2020
DOI: 10.1002/lary.29000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Demographics and Tracheostomy Timing and Technique on Patient Survival

Abstract: Objectives: The ideal timing and technique of tracheostomy vary among patients and may impact outcomes. We aim to examine the association between tracheostomy timing, placement technique, and patient demographics on survival.Study Design: Retrospective cohort study. Methods: A retrospective review was performed for all patients who underwent tracheostomy in 2016 and 2017 at one urban academic tertiary-care hospital. Kaplan-Meier curves were created based on combinations of tracheostomy timing and technique (ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
(65 reference statements)
4
10
0
Order By: Relevance
“…A few studies revealed racial and ethnic differences in adult patients who received a tracheotomy [18][19][20] and in outcomes associated with tracheotomy. 21,22 A study of 86 246 patients with acute brain injury from the National Inpatient Sample database revealed that compared with White patients, Black patients had 20% increased risk of undergoing tracheotomy, Hispanic and Latino patients had 10% increased risk, and Asian patients had 8% increased risk. 20 Furthermore, in a retrospective study of 523 tracheotomies performed at a single institution, multi- variable analyses accounting for age, sex, race and ethnicity, insurance status, income, and comorbidities revealed that Hispanic or Latino ethnicity was associated with increased odds of 30-day mortality after tracheotomy (OR, 4.43; 95% CI, 1.26-15.60).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies revealed racial and ethnic differences in adult patients who received a tracheotomy [18][19][20] and in outcomes associated with tracheotomy. 21,22 A study of 86 246 patients with acute brain injury from the National Inpatient Sample database revealed that compared with White patients, Black patients had 20% increased risk of undergoing tracheotomy, Hispanic and Latino patients had 10% increased risk, and Asian patients had 8% increased risk. 20 Furthermore, in a retrospective study of 523 tracheotomies performed at a single institution, multi- variable analyses accounting for age, sex, race and ethnicity, insurance status, income, and comorbidities revealed that Hispanic or Latino ethnicity was associated with increased odds of 30-day mortality after tracheotomy (OR, 4.43; 95% CI, 1.26-15.60).…”
Section: Discussionmentioning
confidence: 99%
“…1 Although recent studies have considered tracheostomy and optimal timing, [2][3][4] this study is among the first to report primary data on voice, swallowing, and breathing outcomes in patients who underwent tracheostomy for COVID-19 respiratory failure. 4 The study, which provides much needed patient-and clinician-reported measures, underscores the critical role of multidisciplinary teamwork. It also raises pressing questions on how to reduce the incidence and severity of device-related pressure injury during intensive care unit (ICU) stay.…”
Section: Dear Editormentioning
confidence: 96%
“…Recent French guidelines addressed this important question, also underlining that additional data is needed [15]. Only higher body weight [16], presence of comorbidities [17][18][19] and albuminemia levels [20] have previously been associated with worse outcome in tracheostomized patients. In practice, ICU clinicians use clinical judgment and the general health status of the patient to decide whether to perform tracheostomy.…”
mentioning
confidence: 99%